Disponibilidade hídrica na produção de gipsofila (Gypsophila paniculata) em vasos com substrato de casca de arroz carbonizada - Girardi, Leonita Beatriz (2012)
Ornamental plants in general are highly susceptive to water deficiency, principally to the elevated soil water level variation that effects at a precarious and uneven final product development. The study was conducted on greenhouse at the Universidade Federal de Santa Maria, RS. It aimed to observe if rice husk ash substrate offers limitation to the pot cultivation of the specie, to evaluate de the root development under different water availability levels and to analyze the effects on the flower stem qualities and pack yields in two different cultivation periods. The studied specie was Gypsophila paniculata Golan . The seedlings were attained from donor plants at the Floriculture Sector of the Phytotecny Department of UFSM. The experiment was conducted in flexible polyethylene pots with 18 liters of capacity, filled with rice husk ash carbonized on a rice drier mill and kept on 100%, 80%, 60% and 40% of the limit water retention capacity of the pot. The humidity was kept by the weighing method, three times a week (Monday, Wednesday and Friday) the pots were weighted on a decimal precision scale and the difference of the pot weight was added with water to attain the limit established weights to each treatment on the two cultivation periods. The comparison of the production components among the treatments was performed through the variance analyses (ANOVA) significance level of 5% and the regression analyses, because the treatments are quantitative. The comparison between the periods of cultivation was obtained throughout the Tukey Test at the mistake significance level. The results showed that the fine granulometry of the rice husk ash is not a limitation to the cultivation of gypsophila in 18 liters pots. The water consume is higher at the production cycle of spring/summer and it rises with increasing of the water availability, independently the period. The water availability changes the roots spatial distribution in the pot, also changes the length and the dry mass. The commercial quality of the produced stems is not affected importantly by the humidity levels of the substrate or the cultivation cycle. The yield of packs is higher with above 60 % end 80%, humidity for the fall/winter cultivation. However, the 80% of availability provides the best yield.